Dual factor delivery of CXCL12 and Exendin‐4 for improved survival and function of encapsulated beta cells under hypoxic conditions1. Issue 8 (26th March 2013) - Duncanson, Stephanie; Sambanis, Athanassios
Abstract A bioartifical pancreas (BAP) remains a promising approach for treating insulin‐dependent diabetes. Several obstacles to the clinical implementation of a BAP remain, including hypoxia following implantation. Within native pancreatic islets, CXCL12 and glucagon‐like peptide‐1 (GLP‐1) act in a paracrine fashion to promote the survival, function, and proliferation of β‐cells. This work sought to investigate if the presentation of CXCL12 and delivery of a GLP‐1 receptor analog, Exendin‐4 (Ex‐4), alone and in combination, conferred pro‐survival and insulinotropic effects on an encapsulated β‐cell line, βTC‐tet, cultured under hypoxic conditions of 7.6 mmHg O2. Our findings indicate that presentation of CXCL12 in the encapsulation matrix completely abrogated apoptosis under hypoxic conditions. Delivery of Ex‐4 increased insulin secretion rate under both normoxic and hypoxic conditions, and additionally reduced apoptosis under hypoxic conditions. Furthermore, presentation of CXCL12 combined with Ex‐4 delivery significantly increased insulin secretion rate under hypoxic conditions compared to delivery of Ex‐4 alone. These findings demonstrate that the presentation of CXCL12 combined with the delivery of Ex‐4 may constitute a promising strategy for supporting β‐cell function and survival following transplantation. Biotechnol. Bioeng. 2013; 110: 2292–2300. © 2013 Wiley Periodicals, Inc.